Identification of Mathematics Learning Media Needs for Junior High School Students with Hearing Impairment - Megita Dwi Pamungkas; Fadhilah Rahmawati; Yesi Franita; Zuida Ratih Hendrastuti; Aprilia Nurul Chasanah; Arief Budi Wicaksono (STAI Hubbulwathan Duri, 2023)
Students with disabilities face a wide range of obstacles to their academic and personal growth. Because of this, they require educational services tailored to the specific requirements of each student. Even with these disadvantages, deaf pupils must study mathematics. Therefore, there is a need for mathematical learning materials that take into account the specific characteristics and requirements of deaf children. This investigation is a case study of qualitative research. Deaf pupils are the focus of this study. Observation, questionnaires, and in-person interviews were employed to compile the data. In this study, we employ a validity technique known as